Tendon mechanical properties are enhanced via recombinant lysyl oxidase treatment - Nguyen, Phong K.; Jana, Aniket; Huang, Chi; Grafton, Alison; Holt, Iverson; Giacomelli, Michael; Kuo, Catherine K. (Frontiers in Bioengineering and Biotechnology, 2022)
Tendon mechanical properties are significantly compromised in adult tendon injuries, tendon-related birth defects, and connective tissue disorders. Unfortunately, there currently is no effective treatment to restore native tendon mechanical properties after postnatal tendon injury or abnormal fetal development. Approaches to promote crosslinking of extracellular matrix components in tendon have been proposed to enhance insufficient mechanical properties of fibrotic tendon after healing. However, these crosslinking agents, which are not naturally present in the body, are associated with toxicity and significant reductions in metabolic activity at concentrations that enhance tendon mechanical properties. In contrast, we propose that an effective method to restore tendon mechanical properties would be to promote lysyl oxidase (LOX)-mediated collagen crosslinking in tendon during adult tissue healing or fetal tissue development. LOX is naturally occurring in the body, and we previously demonstrated LOX-mediated collagen crosslinking to be a critical regulator of tendon mechanical properties during new tissue formation. In this study, we examined the effects of recombinant LOX treatment on tendon at different stages of development. We found that recombinant LOX treatment significantly enhanced tensile and nanoscale tendon mechanical properties without affecting cell viability or collagen content, density, and maturity. Interestingly, both tendon elastic modulus and LOX-mediated collagen crosslink density plateaued at higher recombinant LOX concentrations, which may have been due to limited availability of adjacent lysine residues that are near enough to be crosslinked together. The plateau in crosslink density at higher concentrations of recombinant LOX treatments may have implications for preventing over-stiffening of tendon, though this requires further investigation. These findings demonstrate the exciting potential for a LOX-based therapeutic to enhance tendon mechanical properties via a naturally occurring crosslinking mechanism, which could have tremendous implications for an estimated 32 million acute and chronic tendon and ligament injuries each year in the U.S.